2003
DOI: 10.1071/ar03072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of beef cattle genotypes and estimation of direct and maternal genetic effects in a tropical environment. 2. Adaptive and temperament traits

Abstract: Data from a crossbreeding experiment conducted during 1992-97 involving 31 genotypes from tropically adapted British (B), Sanga-derived (S), Zebu cross (Zx), Zebu (Z), and Continental (C) beef cattle breed groups on adaptive traits such as mean tick counts (TICK), mean worm egg counts (EPG), mean rectal temperatures (TEMP), and mean coat scores (COAT), and the temperament trait mean flight time (FT) were analysed. The genotypes were grouped as Bos taurus (B, S, C)-and Bos indicus (Z, Zx)-derived to enable the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…Significant heterosis effects have been reported for disease traits in beef cattle where Bos indicus and Bos taurus cattle were crossed (tick and worm resistance, Prayaga, 2003). The general lack of influence of heterosis on disease incidence in this study may be due to less genetic isolation between the breeds of rabbits or simply because there is no consistent heterosis effect for this trait.…”
Section: Time Of Deathmentioning
confidence: 79%
See 1 more Smart Citation
“…Significant heterosis effects have been reported for disease traits in beef cattle where Bos indicus and Bos taurus cattle were crossed (tick and worm resistance, Prayaga, 2003). The general lack of influence of heterosis on disease incidence in this study may be due to less genetic isolation between the breeds of rabbits or simply because there is no consistent heterosis effect for this trait.…”
Section: Time Of Deathmentioning
confidence: 79%
“…After an initial evaluation of the three main meat breeds (Prayaga andEady, 2002, 2003) in Australia (New Zealand White, Californian and Flemish Giant) a selection program began in July 2001. A composite strain of rabbits was established and selection of breeding stock has been based on an index of economic return combining estimated breeding values for litter size at weaning and average daily live weight gain from weeks 5 to 10 of age.…”
Section: Animalsmentioning
confidence: 99%
“…For example, Fell et al ( 1999 ) found that calm animals are less likely to be hospitalized in feedlots than excitable animals, and Reinhardt et al ( 2009 ) showed that mortality rates were higher in excitable than calm steers. However, Burrow ( 2001 ), Prayaga ( 2003 ), and Prayaga and Henshall ( 2005 ) did not find significant relationships between temperament and counts of ticks or flies and fecal egg counts. Reinhardt et al ( 2009 ) did not find any effect of temperament on number of respiratory treatments required or on incidence of lung lesions at slaughter.…”
Section: Genetic Variation Between and Within Breedsmentioning
confidence: 90%
“…Diante de todas essas questões, diversos trabalhos têm sido realizados principalmente no Clay Center (EUA) e também na Austrália (Tropical Beef Cattle) a fim de avaliar o potencial de cruzamentos e formação de bovinos compostos (GREGORY; CUNDIFF; , PRAYAGA, 2003.…”
Section: Bovinos De Corte Compostos E O Sistema Nabcunclassified